Platform power and digital neocolonialism: Netflix and the commodification of local identities in South Korea and Japan - Bagaskara Sagita Wijaya; Sabda Ningsih; Syuryansyah; Muhammad Iqbal Yunazwardi (Faculty of Social and Political Science, Universitas Airlangga, 2026)
This study explores how Netflix, as a digital platform, changes cultural narratives and engages with local identities in Japan and South Korea. It also attempts to comprehend the novel equilibrium between algorithmic supervision and world market opportunities, with an emphasis on repositioning cultural representation as an example of the structural injustices reproduced by the platform. The juxtaposition of Netflix as an economic player and an actor actively participating in the phenomena of identity formation through global market logics is demonstrated by the qualitative data and case studies. It is postulated that increased Korean and Japanese global market representation, by means of identity construction into marketable pieces of informative data, fosters consumerism, paradoxically unidirectional, and agency-attenuating, of a new kind of dependency on Western platforms. The capitalism of a neoliberal global market is hypothesized to be further calculated and enacted by Netflix through its regional productions and alliances, with a new form of net neo-digital colonialism. The complex interplay of algorithmic supervision and structural inequities is an ineluctable reality of digital capitalism, with idiolect equity and legitimacy as the basis. The implications of the findings suggest an extended discourse encompassing digital decolonization and identity restoration.